Antioxidant and cytotoxic activity of black and green tea from Vaccinium meridionale Swartz leaves (2015)
ABSTRACT: Tea is a beverage made from leaves with high contents of polyphenolic substances that vary based on the process they are subjected to. In this study, the apical and young leaves from Vaccinium meridionale (named mortiño) were processed to obtain two kinds of tea: green and black tea. This was done in order to compare their antioxidant activity, content of secondary metabolites at different temperatures of extraction and their antiproliferative effect against SW480 colon cancer cells. Results showed that at 40°C, the green tea infusion presented higher antioxidant activity than the black tea infusion, based on their evaluation using Trolox equivalent antioxidant capacity (TEAC)- diphenylpicrylhydrazyl (DPPH) and oxygen radical absorbance capacity (ORAC) techniques. The green tea also had maximum contents of epicatechin, caffeine, ferulic, chlorogenic and ascorbic acid than the black tea. The total contents of phenols, including hydroxycinnamic acids (caffeic and p-coumaric acid) presented similar results, in both types of tea at the same temperature, as well as the total contents of flavonoids and catechin. When temperatures increased, the extraction of bioactive compounds was more efficient in the black tea infusion than the green tea. This situation led to the increased growth rate per the temperature of the total content of phenols, among which chlorogenic, caffeic and p-coumaric acid were prominent, as well as the corresponding non-polyphenolic substances such as ascorbic acid. The latter may be responsible for the increased antioxidant activity as the temperature increased in the extraction. This antioxidant activity was observed in the black tea from mortiño leaves, using TEAC- DPPH, fluorescence recovery after photobleaching (FRAP) and ORAC assays. Both types of teas had a dose-dependent antiproliferative effect against SW480 colon adenocarcinoma cells. The IC50 of the green and black tea was 26.3 and 36 μg/ml, respectively. These findings suggest that a tea prepared from mortiño leaves may be a promising source of antioxidant and bioactive compounds against coloncancer cells.